2015
DOI: 10.11646/zootaxa.3905.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the world Monoctonia Starý, parasitoids of gall aphids: taxonomy, distribution, host range, and phylogeny (Hymenoptera, Braconidae: Aphidiinae)

Abstract: The present paper represents a contribution to the knowledge of the taxonomy of Monoctonia Starý aphid parasitoids obtained using the barcoding region of the mitochondrial COI gene. We discuss the phylogenetic position of the genus within the subtribe Monoctonina, redescribe known species, and describe Monoctonia japonica sp. n. from Japan in the association Pemphigus matsumurai Monzen/Populus maximowiczii. A key for species identification is provided. Also, we review and discuss the host records, origin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
12
0
3
Order By: Relevance
“…The genus Monoctonia includes three species, all specialized parasitoids of gall forming aphids. A comprehensive revision of the genus is given by Rakhshani et al [10]. The molecular data used in this study show that Monoctonia has a basal position within the subtribe (Figures 4-6).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…The genus Monoctonia includes three species, all specialized parasitoids of gall forming aphids. A comprehensive revision of the genus is given by Rakhshani et al [10]. The molecular data used in this study show that Monoctonia has a basal position within the subtribe (Figures 4-6).…”
Section: Discussionmentioning
confidence: 76%
“…Phylogenetic studies of the subfamily Aphidiinae generally examined only a few Monoctonina species, or entirely excluded them from the analysis [4][5][6][7][8]. In this study, we used sequences of the barcode region of the mitochondrial cytochrome c oxidase subunit I, a gene commonly employed in phylogenetic and taxonomic studies of the Aphidiinae wasps [9][10][11][24][25][26][27]. The second marker used in this study, the nuclear large subunit 28S rDNA, has been used in studies examining phylogenetic relationships within the Braconidae [4,26,[28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Barahoei et al (2011) found that L. fabarum associated with five host aphid species, such as, A. gossypii. Barahoei et al (2011), and Rakhshani et al (2015) also reported parasitisation of aphids by Aphidius spp. and L. fabarum under field conditions.…”
Section: Population Density Of Parasitoid and Hyperparasitoidmentioning
confidence: 94%